2D fluid model for interactive development of ICP technological tools - Gapon, A.V.; Dahov, A.N.; Dudin, S.V.; Zykov, A.V.; Azarenkov, N.A. (Вопросы атомной науки и техники, 2006)
The software for ICP device simulation is worked out. Discharge chamber geometry, RF power, pressure and working gas type are the input data. The results of calculation are inductor voltage, ion current density distribution on the chamber surface, steady state space distributions of the electric field, plasma density and electron temperature in the chamber. Set of 2D parameter distributions is visualized immediately after calculation. The software had been carefully verified by comparing the calculation results with real data measured experimentally. The comparison has shown that both calculated 2D plasma density and electron temperature profiles and ion current density distribution on the processed surface are quite realistic. Graphical geometry input, fast calculation and immediate result visualization makes it possible to use our software for interactive development of ICP technological tools.